Proaromatic pyranylidene chalcogen analogues and cyclopenta[c]thiophen-4,6-dione as electron donors and acceptor in efficient charge-transfer chromophores - Solanke, Parmeshwar Bapurao; Achelle, Sylvain; Cabon, Nolwenn; Pytela, Oldřich; Barsella, Alberta; Caro, Bertrand; Robin-le Guen, Francoise; Podlesný, Jan; Klikar, Milan; Bureš, Filip (Elsevier, 2016)
Fifteen new push-pull chromophores based on a proaromatic pyranylidene donor and its chalcogen analogues and various electron acceptor moieties were synthesized in a straightforward manner. These model molecules were designed and prepared to investigate the concept of proaromaticity as a tool to tune the fundamental properties of push-pull systems. All target chromophores with systematically varied structure were further investigated by electrochemistry, absorption spectra, and EFISH experiment in conjunction with DFT calculations. Employing structural variations such as chalcogen/acceptor replacement, extension of the π-system, and the position of substitution along the pyran ring, the HOMO-LUMO gap can be tuned within the range of 2.18 to 1.41 eV. A new and powerful electron withdrawing moiety, combining features of polarizable thiophene and successful indane-1,3-dione acceptor, cyclopenta[c]thiophen-4,6-dione (ThDione) has also been developed.
Keywords: chalcogenopyranylidene; push-pull; non linear optics; charge transfer; polymethines